PENGARUH PENGGUNAAN MEDIA AUDIOVISUAL POWTOON TERHADAP MOTIVASI DAN HASIL BELAJAR SISWA MATERI UNSUR SENYAWA CAMPURAN - Suhendra, Iin; Enawaty, Eny; Melati, Husna Amalya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrackThe research was aimed to find out the effect of powtoon toward motivation and learning outcomes  on the seventh grade students of SMP Negeri 12 Pontianak about Elements, compounds and mixtures subject material. Purposive sampling used to selecting the sample. The essay test and questionnaire about students? motivation were used as instruments. The posttest results of both class were analyzed using the U-Mann Whitney test with a= 5%. The result showed that the value of  Asymp. Sig (2-tailed) 0.000. It indicated that there was a  difference between learning outcomes in control and experiment class. The questionnaire about students? motivation results of both class were analyzed using the U-Mann Whitney test with a= 5%. It also revealed the value of Asymp. Sig (2-tailed) at 0.000. It indicated that there was the difference students? motivation in control and experiment class. Powtoon as the media in learning procces effected toward the students?learning  outcomes as much as 40.66%.  Kata kunci: Powtoon, Unsur, Senyawa dan Campuran, Motivasi, Hasil Belajar.